2013
DOI: 10.1038/mi.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

TL1A/TNFSF15 directly induces proinflammatory cytokines, including TNFα, from CD3+CD161+ T cells to exacerbate gut inflammation

Abstract: Tumor necrosis factor (TNF)-like cytokine 1A (TL1A)/TNF superfamily member 15 (TNFSF15) is a proinflammatory cytokine and TNFα superfamily member that is linked preclinically and clinically to inflammatory bowel disease (IBD). By homology and function, TNFα is its closest family member. In this study, we investigated the mechanism of TL1A-induced inflammation in CD4+ T cells and compared it with the TNFα pathway. We found that TL1A induces proinflammatory cytokines, including TNFα, from isolated human CD4+CD16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 35 publications
3
63
0
1
Order By: Relevance
“…TNFSF15 is elevated in intestinal tissues and serum of IBD patients (38,39). That the TNFSF15 region rs6478108 A risk allele is a gain of function is consistent with these human and mouse findings.…”
Section: Discussionsupporting
confidence: 77%
“…TNFSF15 is elevated in intestinal tissues and serum of IBD patients (38,39). That the TNFSF15 region rs6478108 A risk allele is a gain of function is consistent with these human and mouse findings.…”
Section: Discussionsupporting
confidence: 77%
“…Treatment with anti-TNF-α agents significantly decreased TNFSF15 serum levels [34]. Similarly, expression of TNFSF15 is increased in the mucosa of inflammatory bowel disease patients [29,30,32]. Several studies suggested that TNFSF15 is a severity factor and that upregulation of TNFSF15 expression can promote mucosal inflammation and gut fibrosis that is caused by increased collagen deposition and number of fibroblasts [31,41].…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with recombinant TNFSF15 caused induction of MMP-9, IL-8 and TNF-α in several cell types [29,35,39]. These mediators are implicated in the progression of PDR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations